2014
DOI: 10.1007/978-3-319-08927-0_10
|View full text |Cite
|
Sign up to set email alerts
|

Altered Galectin Glycosylation: Potential Factor for the Diagnostics and Therapeutics of Various Cardiovascular and Neurological Disorders

Abstract: Galectins are β-galactoside binding mammalian proteins characterized by the presence of a conserved carbohydrate recognition domain, expressed in almost all taxa of living organisms and involved in broad range of significant biological and physiological functions. Previously, we reported the purification and extensive characterization of galectin-1 from goat (Capra hircus) heart. Interestingly, the purified protein was found to have significant level of glycosylation. This intrigued us to evaluate the involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Gal-3 functional roles have been reported in CNS ( Bresalier et al, 1997 ; Reichert and Rotshenker, 1999 ). Gal-3 inductions are evident in various pathological processes of brain diseases such as prion diseases, ALS, AD, ischemic brain lesions, and PD ( Jin et al, 2007 ; Lerman et al, 2012 ; Ashraf et al, 2015 ). The possible physiological role of Gal-3 in AD and ALS can be investigated by exploring its already established biological functions like their role in inflammation and apoptosis (extracellular Gal-3 being proapoptotic, and intracellular Gal-3 being anti-apoptotic) ( Yu et al, 2002 ; Nangia-Makker et al, 2007 ; Henderson and Sethi, 2009 ; Ashraf et al, 2010a ; Siwicki et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gal-3 functional roles have been reported in CNS ( Bresalier et al, 1997 ; Reichert and Rotshenker, 1999 ). Gal-3 inductions are evident in various pathological processes of brain diseases such as prion diseases, ALS, AD, ischemic brain lesions, and PD ( Jin et al, 2007 ; Lerman et al, 2012 ; Ashraf et al, 2015 ). The possible physiological role of Gal-3 in AD and ALS can be investigated by exploring its already established biological functions like their role in inflammation and apoptosis (extracellular Gal-3 being proapoptotic, and intracellular Gal-3 being anti-apoptotic) ( Yu et al, 2002 ; Nangia-Makker et al, 2007 ; Henderson and Sethi, 2009 ; Ashraf et al, 2010a ; Siwicki et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, it is well accepted that GALs can regulate numerous cell function such as inflammation and survival by regulating various cell signaling pathways (Ashraf et al, ; Ashraf, Perveen, Tabrez, et al, ; Ashraf, Perveen, Zaidi, et al, ). GAL‐3 was shown to stimulate cell survival through activation of Akt and NF‐κB signaling and plays a crucial role in promoting tumorigenesis and drug resistance of various tumors including OC (Mirandola, Yu, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, available literature reports relevant roles of galectins (GALs) in modulation of acute inflammatory response and protection against several disorders (Ashraf, Mahmoud, & Tabrez, ; Ashraf, Perveen, Tabrez, et al, ; Ashraf, Perveen, Zaidi, et al, ). Galectin‐3 (GAL‐3) (coded by LGALS3 gene) is an S‐type lectin that binds β‐galactose‐containing glycoconjugates and is highly expressed on the surface, nuclei, and cytoplasm of the cells and is abundantly found in the circulation (Mirandola, Yu, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Two intracellular enzymes, O-GlcNAc transferase (OGT) and O-GlcNAcase (OGA), mediate addition and removal, respectively, of O-GlcNAc glycosylation from intracellular protein substrates [27]. Ashraf et al reported that goat heart Gal-1 with GlcNAc glycosylation had protection against damage and denaturation by biologically active chemicals as compare to the deglycosylated form [28]. In this study, Gal-7 expression reduction was not only observed at protein levels but also at mRNA levels after exposing keratinocytes to high-glucose environment.…”
Section: Discussionmentioning
confidence: 99%